2016
DOI: 10.1007/s13239-016-0269-7
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Blood Flow Through Arteries Following Atherectomy and the Impact on Pressure Variation and Velocity

Abstract: Simulations were made of the pressure and velocity fields throughout an artery before and after removal of plaque using orbital atherectomy plus adjunctive balloon angioplasty or stenting. The calculations were carried out with an unsteady computational fluid dynamic solver that allows the fluid to naturally transition to turbulence. The results of the atherectomy procedure leads to an increased flow through the stenotic zone with a coincident decrease in pressure drop across the stenosis. The measured effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 73 publications
2
7
0
Order By: Relevance
“…Both the high pressure and the narrowing of blood vessels cause high flow velocity, high shear stress, and low or negative pressure at the throat of the stenosis [1]. Stenosis may create significant flow resistance and a large pressure drop [5,25]. Our results are found to be in excellent agreement with these facts.…”
Section: Discussionsupporting
confidence: 80%
“…Both the high pressure and the narrowing of blood vessels cause high flow velocity, high shear stress, and low or negative pressure at the throat of the stenosis [1]. Stenosis may create significant flow resistance and a large pressure drop [5,25]. Our results are found to be in excellent agreement with these facts.…”
Section: Discussionsupporting
confidence: 80%
“…Since blood is considered an isotropic Newtonian and laminar flow in the coronary arteries where the drug-eluting stents are typically implanted [14,9], we will assume the steady Navier-Stokes equations to model blood flow in the lumen. In fact, as discussed, e.g., in [2,28], the relevance of non-Newtonian effects in midsize arteries is negligible. For plasma filtration through the wall, assuming that both the intima and the media layers are porous media with isotropic and uniform permeability, we assume the Darcy equation.…”
mentioning
confidence: 85%
“…Derivation of the solution. In this appendix we calculate the solution of the problem (25)-(28) presented in section 3. Letc 1 represent the Laplace transform of c 1 ; then from(25) and(26) we deduce∂ 2c 1 ∂x 2 (x, s) − λ 2 (s)c 1 (x, s) = − c 0 λ 2 (s) using the method of variation of parameters yields c 1 (x, s) = C 1 (s)e −λ(s)x + C 2 (s)e λ(s)x + c 0 s .From the boundary condition(27) we get thatc 1 (x, s) = C 1 (s) cosh (λ(s)x) + c 0 s ,(73)while from(28) it follows thatC 1 (s) = c out s − c 0 s 1 cosh (λ(s)L).Substituting the previous expression for C1 (s) into (73) gives c 1 (x, s) = c out cosh (λ(s)x) s cosh (λ(s)L) + c 0 (cosh (λ(s)L) − cosh (λ(s)x)) s cosh (λ(s)L) .…”
mentioning
confidence: 99%
“…Even so, [39] studied analytically the transport of Low-Density Lipoprotein through an arterial wall under hyperthermia conditions using a four-layer model, and had results that are in excellent agreement with existing numerical and analytical literature data under isothermal conditions. [40] considered blood flow through arteries under atherectomy situation using an unsteady computational fluid dynamic solver, and found that the atherectomy procedure tends to increase the flow through the stenotic zone.…”
Section: Introductionmentioning
confidence: 99%